(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2019)
An experiment was carried out at the Agronomy Field, Sher-e-Bangla Agricultural University, Dhaka during November 2009 to July 2010 to study the effect of variety and varying levels of nitrogen application to ratoon crop of boro rice. Four varieties (BRRI hybrid dhan2, BRRI dhan29, BRRI dhan35 and BRRI dhan47) and four doses of nitrogen (0%, 25%, 50% and 75% N of recommended dose) were tested. These doses of N fertilizer were applied to the ratoon crop just after harvesting of the main crop leaving 15 cm stuble height above the ground level. Among the main crop BRRI hybrid dhan2 produced significantly highest grain yield (7.037 t ha-1). In the ratoon crop grain yield of BRRI hybrid dhan2 and BRRI dhan29 with all levels of N application produced significantly higher grain yield (710-917 kg ha-1). So, BRRI hybrid dhan2 and BRRI dhan29 with 25% extra N application could be considered for ratoon cropping. Int. J. Agril. Res. Innov. & Tech. 9 (1): 48-57, June, 2019